2018
DOI: 10.1007/s00228-018-2531-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypnotic use at 10 years—does the brand matter?

Abstract: One in five new users of sedative-hypnotics will become a long-term user, but only 0.5% will become excessive users. Z-drugs were associated with an increased risk of chronic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 51 publications
0
29
0
2
Order By: Relevance
“…Misuse, abuse or dependence on zolpidem is a worldwide problem [25][26][27]. In France, regulatory changes such as the addition of prescription constraints seem to have a higher impact on prescriptions than the information for physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Misuse, abuse or dependence on zolpidem is a worldwide problem [25][26][27]. In France, regulatory changes such as the addition of prescription constraints seem to have a higher impact on prescriptions than the information for physicians.…”
Section: Discussionmentioning
confidence: 99%
“…In another study where PCPs reported patient data, we found a lower rate of phytopharmaceutical and high rate of BZD use in Swiss primary care chronic insomnia patients (Maire et al., 2020). One hypothesis might be that PCPs initially prescribed phytopharmaceuticals and then, because patients do not respond to this treatment, felt entitled to switch patients to the more effective hypnotics, even though that meant potential long‐term treatment and addiction (Schonmann et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with an increased prevalence of Z-drugs, which steadily rose, e.g., in the United States from 0.05% in 1999−2000 to 0.47% in 2013−2014, by reflecting absolute and relative increases of +0.42% and +840% [8]. Moreover, even if guidelines recommend a short-term use (no more than 4 weeks), Z-drugs have been demonstrated to be associated with an increased risk of chronic use [2,[9][10][11].…”
Section: Introduction Backgroundmentioning
confidence: 99%